A eutanásia imposta pela metrópole: Notas sobre Camere separate, de pier vittorio tondelli, e pela noite, de caio fernando abreu - De Sousa Serafim, Lucas [UNESP] (My University, 2014)
This text intended to reflect on the experiences of death, imposed by the urban context based on some of the philosophical theories of Maurice Blanchot, applied in two literary works of authors Caio Fernando Abreu and Pier Vittorio Tondelli.
Euthanasia imposed by the city: Notes on Pier Vittorio Tondelli's Camere separate and Caio Fernando Abreu's Pela noite